BENTUK AFIKS DALAM LIRIK LAGU SEDIA AKU SEBELUM HUJAN KARYA IDGITAF KAJIAN MORFOLOGI - Dina Sri Puspitasari; Dinda Wulansari; Khusnul Nur Mawar Sari; Mita Miftaqul Muhclisah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to examine the word formation process through affixation in the lyrics of the song "Sedia Aku Sebelum Hujan" by Idgitaf. Affixation is a morphological process that plays an important role in expanding word meanings and forming variations in language structure in a text, including song lyrics. The use of affixes in song lyrics not only functions as a linguistic structure but also as a means to emphasize messages, describe emotions, and enrich the aesthetic nuances that the songwriter wants to convey. This research uses a qualitative descriptive method with note-taking analysis techniques. The research data is in the form of affixed words collected from the lyrics of the song "Sedia Aku Sebelum Hujan," then analyzed based on the type of affix, namely prefix, suffix, infix, and confix. The results showed that there are 17 affixed words in the lyrics, consisting of 7 prefixes, 9 suffixes, 0 infixes, and 1 confix. The dominant use of suffixes, especially -kan and -mu, indicates their functional role in forming transitive verbs and marking grammatical relations in the lyrical context